REG γ knockdown suppresses proliferation by inducing apoptosis and cell cycle arrest in osteosarcoma - Yin,Zhiqiang; Jin,Hao; Huang,Shibo; Qu,Guofan; Meng,Qinggang (PeerJ, 2020)
Background Osteosarcoma (OS) is the most common malignant bone tumor with high mortality in children and adolescents. REG γ is overexpressed and plays oncogenic roles in various types of human cancers. However, the expression and potential roles of REG γ in osteosarcoma are elusive. This study aims at exploring possible biological functions of REG γ in the pathogenesis of osteosarcoma and its underlying mechanism. Methods Quantitativereverse transcription-polymerase chain reaction (qRT-PCR), western blotting andimmunohistochemistry (IHC)were performed to detect the expression levels of REG γ in OS tissues and cell lines. Then, the effects of REG γ expression on OS cell proliferation in vitro were analyzed by Cell Counting Kit-8 (CCK-8), ethylene deoxyuridine (EdU), colony formation, flow cytometry. The protein levels of apoptosis and cell-cycle related proteins were evaluated using western blotting. Results In present study, we found for the first time that REG γ is overexpressed in osteosarcoma tissues and cell lines and knockdown of REG γ significantly inhibits cell proliferation and induces apoptosis and cell cycle arrest in osteosarcoma cells. Furthermore, we observed that p21, caspase-3 and cleaved caspase-3 are increased while the expression of cycinD1 and bcl-2 are decreased after REG γ depletion in osteosarcoma cells. In conclusion, REG γ may be involved in the proliferation of osteosarcoma and serve as a novel therapeutic target in patients with osteosarcoma.
Keywords: Osteosarcoma; Proliferation; REG γ